2014
DOI: 10.1007/s00005-014-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Induced Hypertension is Accompanied by Decreased Number of Circulating Endothelial Cells and Circulating Endothelial Progenitor Cells

Abstract: Maternal endothelial dysfunction is one of the main features of pregnancy-induced hypertension (PIH). It is generally accepted that circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) reflect the state of the endothelium, its injury and/or repair possibilities. The objective of this study was to determine whether the CECs and EPCs numbers in the circulation of women with PIH reflect the presence of this pathology. Peripheral blood cells of PIH and normotensive pregnant women were label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…26 When we compared the women in the gestational hypertension group with those in the control group, our findings revealed no statistically significant differences in the number of CECs. However, in a recent study, Heimrath et al 27 have indicated that women with gestational hypertension have lower levels of CECs compared to women with healthy pregnancies. The course of gestational hypertension is usually mild, and in our findings, the blood pressure values in the gestational hypertension group were the lowest of the different study groups.…”
Section: Circulating Endothelial Cells (Cecs)mentioning
confidence: 94%
“…26 When we compared the women in the gestational hypertension group with those in the control group, our findings revealed no statistically significant differences in the number of CECs. However, in a recent study, Heimrath et al 27 have indicated that women with gestational hypertension have lower levels of CECs compared to women with healthy pregnancies. The course of gestational hypertension is usually mild, and in our findings, the blood pressure values in the gestational hypertension group were the lowest of the different study groups.…”
Section: Circulating Endothelial Cells (Cecs)mentioning
confidence: 94%
“…To evaluate EPC number (CD34 + , VEGFR2/ KDR + ), PerCP-conjugated anti-CD34 (Becton Dickinson) and PE-conjugated anti-VEGFR2/KDR (R&D Systems) antibodies were used. Cells were labeled like described by Heimrath et al 22 Minimal counts of 150,000 events were collected. Fluorescence-activated cell sorting analyses were performed using CellQuest software (Becton Dickinson) and fluorescent CytoCount beads (Dako) for cell number evaluation.…”
Section: Flow Cytometry Analysis Of Cec and Epc Numbers In Peripheralmentioning
confidence: 99%
“…21 We showed that, in young pregnant women with pregnancy-induced hypertension, EPC number was significantly diminished as compared with the control group of healthy pregnant women. 22 The endometrium is the mucous layer of human uterus composed of a layer of epithelium and a layer of connective tissue, the thickness of which changes according to the age and hormonal status from 0.5 mm in young, nonmenstruating woman to approximately 7 to 15 mm during the menstrual cycle. In postmenopausal women taking hormonal replacement therapy, endometrium thickness should not exceed 8 mm.…”
mentioning
confidence: 99%
“…In hypertensive individuals with end-stage renal disease, EPC number and function were significantly reduced and inversely associated with CV risk [82] . Moreover, the levels of EPCs in the peripheral blood of women with pregnancy-induced hypertension were significantly lower compared with those of control pregnant women with normal BP level [83] . Numerous investigators reported that a lowered number of EPC and an altered EPC function related strongly not only with brachial BP levels, but the increased central aortic systolic pressure, aortic augmentation index, and pulse wave velocity as a marker of arterial stiffness.…”
Section: The Diagnostic and Prognostic Values Of Epcs In Hypertensionmentioning
confidence: 77%